Undocumented and unwanted : attending college against the odds - Garcia, Lisa DeAnn (New Americans (LFB Scholarly Publishing LLC), 2013)
Undocumented immigrant postsecondary students face myriad challenges while pursuing a college education. Garcia focuses on the experiences of nine students attending a public comprehensive postsecondary institution in California to assess how different types of social capital help students pursue a college education. She demonstrates how students were wholly or partly reliant on various types of social capital accessed before and during matriculation. Three of the major findings are: institutional agents were instrumental in developing students' social capital, family- and peer-based social ...